Optical coherence tomography findings in a case of cilioretinal artery occlusion reversal, treated with mannitol and carbogen administration - Christodoulou, Panayiotis; Katsimpris, Ioannis (Annals of Eye Science, 2019)
To present spectral domain optical coherence tomography (OCT) findings during treatment in a case of acute isolated cilioretinal artery occlusion (CLRAO) reversed with intravenous systemic administration of mannitol and carbogen inhalation. Close monitoring with OCT thickness topographic map and cross section scans, every 12 hours, during treatment and till complete reversal of retinal nerve fiber layer edema. Fundus photography and fluorescein angiography (FFA) were used to illustrate occlusion and recanalization. After 72 hours of therapy, visual acuity improved from counting fingers (CF) to 7/10, Snellen’s chart. Consecutively OCT scans showed that the initial macular edema was gradually restored to typical 72 hours of treatment initiation. FFA performed after treatment confirmed recanalization of the cilioretinal artery. Early intervention with the combined intravenous administration of mannitol and carbogen inhalation can reverse acute onset loss of vision due to CLRAO. The reflectivity of retinal layers differs significantly regarding stages of acute CLRAO. In our case report increased reflectivity of the innermost layers of the retina was illustrated and a corresponding reduction in the outer retina and the retinal pigment epithelium and choriocapillaris layers. Macular thickness follow-up data recorded the course of intracellular edema to normal.